Determinants and costs of community nursing in patients with type 2 diabetes from a community-based observational study: The Fremantle Diabetes Study - Davis, W.; Lewin, Gill; Davis, T.; Bruce, D. (Elsevier Ltd, 2013)
Background: Despite widespread use, there is little information on the extent and impact of community nursing to patients with type 2 diabetes. Objective: To determine the incidence, predictors and costs of community nursing provision to patients with type 2 diabetes in a large community-based representative study of diabetes in an urban Australian setting. Design: Prospective observational study utilising data linkage. Setting: Postcode defined region in Fremantle, Australia. Participants: All patients with type 2 diabetes enrolled in the Fremantle Diabetes Study between 1993 and 1996. Methods: Eligible patients were followed from July 1997, when home nursing data first became available, to death or census in November 2007. Home nursing data from the major community nursing service provider were linked with data from the Fremantle Diabetes Study. Cox and zero-inflated negative binomial (ZINB) regression modelling was used to identify predictors of incident home visits and visit frequency, respectively. Direct costs were estimated from the service provider's unit costs.Results: During a mean ± SD 8.6 ± 2.9 years of follow-up, 27.8% of 825 patients (aged 65.2 ± 10.3 years at study entry; 51.2% male) received 21,878 home nursing visits (median frequency 31 [interquartile range 9–85] visits, range 1–1446 visits). In Cox and ZINB models, predictors of home nursing included older age, physical disability measures and macrovascular and microvascular complications. Insulin use was an important predictor of the frequency of visits whilst ethnic and economic factors predicted lower frequency. The estimated cost of home nursing, extrapolated nationally, adds 5% to the total Australian direct health care costs of diabetes. Conclusions: Home nursing is frequently utilized in the management of type 2 diabetes with considerable individual variation in the use of this service. Given the associated costs, further research into how home nursing can best be employed is indicated.